Snail Shell-Reinforced Waste-Based Polymer Composites for Radiation Shielding and Anti-Reflective Applications - Pekdemir, Mustafa Ersin; Pekdemir, Sibel Selcuk; Yilmaz, Demet; Onay, Hatice; Qader, Ibrahim Nazem (Mdpi, 2025)
The increasing demand for sustainable and multifunctional materials in radiation shielding and optical applications has driven research toward utilizing natural and waste-derived reinforcements in polymer matrices. However, achieving effective attenuation performance across different radiation types using eco-friendly fillers remains a significant challenge. In this study, polyvinyl chloride (PVC)/Polystyrene (PSt) blend composites (1:1 weight ratio) were reinforced with powdered snail shell (SSP) as a biogenic additive, aiming to enhance their shielding and optical performance. Composites containing 5%, 10%, 20%, and 30% SSP (w/v) were fabricated and characterized. Key parameters including linear attenuation coefficient (LAC), mass attenuation coefficient (MAC), mean free path (MFP), half-value layer (HVL), and effective atomic number (Zeff) were measured using a variable-energy X-ray source (13.37-59.54 keV) and ULEGe detector. Fast neutron shielding performance and theoretical values for build-up factor (EBF) and macroscopic neutron cross-sections were also calculated. The results showed a marked improvement in X-ray attenuation with increasing SSP content (SSP30 > SSP20 > SSP10 > SSP5), while neutron shielding declined due to the high oxygen content of SSP. Among the tested samples, the SSP30 composite exhibited the highest X-ray attenuation efficiency, whereas the SSP5 composition showed the greatest enhancement in optical reflectance and neutron absorption, indicating optimal performance in these respective tests. Additionally, 5% SSP incorporation improved optical reflectance by 12%, indicating enhanced photon backscattering at the material surface. This behavior contributes to improved gamma shielding efficiency by reducing photon penetration and enhancing surface-level attenuation. These findings highlight the potential of snail shell-based fillers as low-cost, sustainable reinforcements in multifunctional polymer composites.
Keywords: polyvinyl chloride (PVC); polystyrene blend; snail shell powder; radiation shielding composites; anti-reflective materials; waste-derived filler